Seed security in Badakshan, Afghanistan - Kermali, Iqbal (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Badakshan is located in the extreme northeastern comer of Afghanistan and has not yet come under Taliban control. The province is virtually cut off from the rest of the country and is traditionally food deficient. The 20-year-old conflict in the region has further aggravated the situation, causing massive population displacement and al most complete destruction of civil institutions and infrastructure. The situation has become so serious that food aid has to be distributed in the period of grain deficit, starting from before the harvest. Simultaneously, efforts are being made to rehabilitate and improve the agricultural systems of these farming communities.